Integrating a virtual simulator in a large-scale live exercise : Lessons learned regarding training and operations aspects - Petermeijer, S.M.; Thijssen, D.; Lubsen, Z.A.; Lemmers, A.J.J. (Clarion Defense & Security, 2024)
LVC training for fighter pilots has been argued to reduce training cost, enrich training scenarios and to be flexible and scalable. An LVC environment with a high level of interoperability requires a dedicated datalink to exchange training data with a high throughput and low latency. Research and development regarding the standardization of such links and technology is ongoing, but it is unlikely an highly interoperable LVC environment will become prevalent in the coming years. Fortunately, a highly interoperable LVC environment is not required to enhance the relatively small-scale training scenarios which are typically used during day-to-day training. Using existing technologies and operational datalinks effective LVC training can be facilitated, albeit with a reduced level of interoperability and limited set of possible interaction between the entities. Training experts agree that even a slight enhancement of the live day-to-day training might provide relatively large training benefits. The goal of this research is to investigate how day-to-day training can be facilitated without major changes to the training organisation and investment and to what extend such a set-up can offer in terms of training benefits. In October 2023 a synthetic environment – consisting of a virtual fighter and several constructive entities – was integrated into a large-scale international live flying exercise. The synthetic and live entities were able to exchange data through an operational Link-16 datalink. The virtual simulator joined the training scenario as a two-ship and supported the live players in their Offensive and Defensive Counter Air missions. After the training exercises the perceived added training value, for the live pilots as well as the pilot in the simulator, was evaluated through questionnaires and interviews. A detailed analysis of the results and a synthesis of the lessons learned is currently being performed. Preliminary results show that the virtual simulator and constructive entities add to the perceived training value of the live pilots. Moreover, the pilots of the virtual simulator also experienced training value in the simulator, albeit of a reduced magnitude. The preparation and operation of the LVC environment required too much technical support to offer a realistic option for day-to-day training in the current setup, but these are foreseen to be surmountable without excessive effort. Finally, the paper describes the design of a LVC environment in more detail, the training value such a setup is foreseen to offer, and the operational requirements in order to be effectively integrated in day-to-day training.